2021
DOI: 10.1007/s40843-021-1779-7
|View full text |Cite
|
Sign up to set email alerts
|

Highly sensitive light-up near-infrared fluorescent probe for detection and imaging of β-glucuronidase in human serum, living cells and tumor-bearing mice

Abstract: β-Glucuronidase (GUS) plays a key role in tumor initiation, metastasis, and progression, and thus, has been proposed as a promising cancer biomarker. In this study, we designed an enzyme-activatable near-infrared (NIR) fluorescent probe (DCM-βGlcA) for the rapid and accurate detection of GUS activity in vitro, in vivo and ex vivo. The DCM-βGlcA was prepared by linking a glucuronic acid residue to dicyanomethylene-4H-pyran (DCM). This probe exhibited significant light-up NIR fluorescent signals at 680 nm after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…α-Fuc-DCM was assembled of α-L-fucose monosaccharide, as the AFU-selective recognition unit, with a dicyanomethylene-4H-pyran (DCM) chromophore, as the fluorogenic reporter owing to its excellent sensing properties. [28,29] When exposure to AFU, the biosensor exhibited a gradual increase of fluorescence intensity in the NIR region. By using this biosensor, the intracellular distribution of endogenous AFU was successfully detected.…”
Section: Introductionmentioning
confidence: 99%
“…α-Fuc-DCM was assembled of α-L-fucose monosaccharide, as the AFU-selective recognition unit, with a dicyanomethylene-4H-pyran (DCM) chromophore, as the fluorogenic reporter owing to its excellent sensing properties. [28,29] When exposure to AFU, the biosensor exhibited a gradual increase of fluorescence intensity in the NIR region. By using this biosensor, the intracellular distribution of endogenous AFU was successfully detected.…”
Section: Introductionmentioning
confidence: 99%
“…To date, over 80% of the fluorescent probes used in clinical trials are "always-on" probes, emitting fluorescence regardless of their interactions with target tissues, thus resulting in non-specificity and a low tumor-to-normal tissue ratio (TNR) [13,14]. In contrast, stimulus-activatable fluorescent probes are not fluorescent until they are activated by specific tumor biomarker (E.g., overproduced enzymes, low pH) and are promising for in vivo imaging [15][16][17]. 5-Aminolevulinic acid (5-ALA) was the only "off-on" probe used clinically, which can elicit the synthesis of fluorescent protoporphyrin IX in cancer cells [18].…”
Section: Introductionmentioning
confidence: 99%
“…β-Glucuronidase (GLU), lysosomal glycosidase, is an important biologically active protease that exists in the human body. GLU is mainly involved in the degradation of glycosaminoglycans containing glucuronides and is related to a variety of pathophysiological conditions in the organism. , In addition, GLU is also a tumor biomarker, and the active expression of GLU is closely related to tumor cell invasion, apoptosis, metastasis, and proliferation. Studies have shown that, compared with normal liver cells when liver cells become cancerous, the activity of GLU in liver tissues is significantly enhanced. In the normal liver detoxification process, toxic substances are combined with glucuronides under the action of uridine 5′-diphospho-glucuronosyltransferase to form hydrophilic substances that are eliminated from the body. In contrast, in cancerous liver cells, the overexpression of GLU will cause glucuronides to be overly decomposed and lose their ability to bind to harmful substances. , In the end, it is difficult for the organism to exclude the hydrophobic harmful substances from the body and the long-term accumulation of toxic substances in the organism results in the body’s pathological changes. ,, This is also an important reason why GLU has become a target for real-time monitoring and the early diagnosis of liver cancer. Therefore, developing a method to accurately detect and analyze GLU is the problem that researchers must solve.…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescence imaging technology has become a hot spot in public research, because of its simple operation, low cost, high sensitivity, and low detection limit. Several fluorescent probes have been reported for the detection of GLU activity, but they are limited to the use of hydroxyl-containing dyes as luminophores. ,,, However, the use of self-sacrificing spacers can increase the variety of luminophore choices, such as the use of amino-containing fluorescent dyes. Here, we have constructed a series of fluorescent probes DCDH , DCDCH 3 , DCDOCH 3 , and DCDNO 2 for real-time precision detection of GLU.…”
Section: Introductionmentioning
confidence: 99%